Nursing Students' Experience on Internet Using: The Voice of Generation Z - Amalia, Raisya; Raden, Najla Salsabila (Faculty of Teacher Training and Education, 2025)
This study aims to describe the experiences of Generation Z university students towards using the internet in their academic life. Using a descriptive survey method involving 103 respondents, the results show that most students use the internet regularly, both for academic purposes and to avoid negative emotions. As many as 78% of respondents use the internet for academic purposes, while some experience negative impacts, such as sleep disturbances and psychological discomfort. In conclusion, internet use has significant benefits in supporting academics, but also requires regulation to prevent negative impacts, including addiction.